Clinical and perinatal outcomes of fresh single-blastocyst-transfer cycles under an early follicular phase prolonged protocol according to day of trigger estradiol levels - Ying, Yingfen (PeerJ, 2021)
BACKGROUD: This study’s objectives were to compare the clinical, perinatal, and obstetrical outcomes of patients with different estradiol (E(2)) levels in fresh single-blastocyst-transfer (SBT) cycles under an early follicular phase prolonged regimen on the day of trigger. METHODS: We recruited patients in fresh SBT cycles (n = 771) undergoing early follicular phase prolonged protocols with β-hCG values above 10 IU/L between June 2016 and December 2018. Patients who met the inclusion and exclusion criteria were divided into four groups according to their serum E(2) level percentages on the day of trigger: <25(th), 25(th)–50(th), 51(st)–75(th), and >75(th) percentile groups. RESULTS: Although the rates of clinical pregnancy (85.57% (166/194)), embryo implantation 86.60% (168/194), ongoing pregnancy (71.13% (138/194)), and live birth (71.13% (138/194)) were lowest in the >75th percentile group, we did not observe any significant differences (all P > 0.05). We used this information to predict the rate of severe ovarian hyperstimulation syndrome (OHSS) area under the curve (AUC) = 72.39%, P = 0.029, cut off value of E(2) = 2,893 pg/ml with the 75% sensitivity and 70% specificity. The 51(st)–75(th) percentile group had the highest rates of low birth weight infants (11.73% (19/162), P = 0.0408), premature delivery (11.43% (20/175), P = 0.0269), admission to the neonatal intensive care unit (NICU) (10.49% (17/162), P = 0.0029), twin pregnancies (8.57% (15/175), P = 0.0047), and monochorionic diamniotic pregnancies (8.57% (15/175); P = 0.001). We did not observe statistical differences in obstetrics complications, including gestational diabetes mellitus (GDM), gestational hypertension, placenta previa, premature rupture of membranes (PROM), and preterm premature rupture of membranes (PPROM). CONCLUSION: We concluded that serum E(2) levels on the day of trigger were not good predictors of live birth rate or perinatal and obstetrical outcomes. However, we found that high E(2) levels may not be conducive to persistent pregnancies. The E(2) level on the day of trigger can still be used to predict the incidence of early onset severe OHSS in the fresh SBT cycle.